Fish Diversity of Ghodaghodi Lake Area: An Important Ramsar Wetland Site, Kailali, Far-Western, Nepal - K.C., Laba; Shrestha, Santoshi; Sigdel, Prakash; Chaudhary, Dayaram (Journal of Institute of Science and Technology, 2023)
Fish diversity of Ghodaghodi Lake Area (Ghodaghodi and Nakhrod Lake) from April 2019 to August 2021, covering three seasons; Pre-monsoon (April 2019), Post-monsoon (February 2020), and Monsoon (July 2021) by using conventional and locally accessible fishing gears such as gill nets, cast nets and hook lines in 17 sampling points. A total of 2810 individuals with 39 species, 27 genera, 19 families, and 8 orders were documented. The most common fish species were Pethia ticto, Xenentodon cancila, Notopterus notopterus, Nandus nandus, and Pethia conchonius. The order Cypriniformes accounts for the majority of both Ghodaghodi (42%) and Nakhrod Lake (33%) respectively. The diversity indices were found to be higher in the pre-monsoon season in both Ghodaghodi Lake (2.58) and Nakhrod Lake (1.85), whereas lower in post-monsoon (2.36) in Ghodaghodi Lake and monsoon (1.35) in Nakhrod Lake. Similarly, species richness was highest in the monsoon season (9.33) in Ghodaghodi Lake and pre-monsoon season (3.29) in Nakhrod Lake while it was lowest in the post-monsoon season (4.19), (2.25) in Ghodaghodi and Nakhrod Lake respectively. Likewise, the evenness value for Ghodaghodi and Nakhrod Lake was found to be higher in the pre-monsoon season (0.95), (0.92) and lower in the monsoon season (0.79), (0.68) in Ghodaghodi and Nakhrod Lake, respectively.